A Rare Cause of Acute Kidney Injury in a Female Patient with Breast Cancer Presenting as Renal Colic - Roxana Jurubita; Bogdan Obrisca; Gener Ismail (Case Reports in Nephrology)
Renal infarction is a rare cause of acute kidney injury which could lead to permanent loss of renal function. A prompt diagnosis is necessary in order to achieve a successful revascularization of the occluded artery. Given the rarity of the disease and the paucity of the reported cases in the previous literature a high index of suspicion must be maintained not only in the classical cardiac sources of systemic emboli (atrial fibrillation, dilated cardiomyopathy, or endocarditis), but also in the situations when a hypercoagulable state is presumed. The unspecific presenting symptoms often mask the true etiology of the patient’s complaints. We present here a rare case of renal infarction that occurred in the setting of a hypercoagulable state, in a female patient with a history of breast cancer and documented hepatic metastases.